Tinjauan Implementasi Rekam Medis Elektronik Rawat Jalan Guna Menunjang Efektivitas Pelayanan Di RSUD Majalaya - Adika Wardana Giantara; Wowo Trianto (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Advances in information technology have brought significant changes to healthcare delivery, one of which is the implementation of Electronic Medical Records (EMR) in various healthcare facilities. EMR has become an important component in improving the quality of medical data, patient safety, and service effectiveness. However, its implementation still faces various challenges, especially in regional hospitals such as Majalaya Regional General Hospital. This study aims to analyze the EMR implementation process, system quality, and the challenges and solutions encountered in the system's application at RSUD Majalaya. The study employs a qualitative method with a descriptive approach through in-depth interviews with six key informants: the Medical Records Manager, Medical Records Officer, Coding Officer, Nurse, Reporting Officer, and IT Officer. The results of the study indicate that the implementation of EMR is beneficial in accelerating access, processing patient data, and facilitating the reporting process. However, challenges were identified in terms of infrastructure, lack of system proficiency, and the need for further training and technical support. It is recommended that there be an increase in human resource training and infrastructure strengthening to ensure the optimal utilization of EMR at RSUD Majalaya.